Antioxidant compounds in hawthorn fruits (Crataegus spp.) of Mexico - Maria del Rosario García-Mateos; Emmanuel Ibarra-Estrada; Raúl Nieto-Ángel (Revista Mexicana de Biodiversidad)
The content of phytochemicals associated with the antioxidant activity of the fruits of species of hawthorn (Crataegus spp.; Rosácea) located in Mexico is unknown. The objective of the present study was to evaluate the content of phenolic compounds, flavonoids, vitamin C and the antioxidant activity in a selection of Mexican hawthorn species. A quantification was made of total phenols, flavonoids and vitamin C (expressed on mg of phenol, quercetin and ascorbic acid per 100 g of fresh weight, respectively), in 20 selected samples of hawthorn fruits located in the germ plasm bank of the Universidad Autónoma Chapingo, Mexico. The antioxidant activity as evaluated by the DPPH method, expresses as mean inhibitory concentration (IC50). No correlation was observed of the content of phenols, flavonoids and vitamin C with the origin and species of the samples. Some of the samples from the state of Chiapas could be considered to have a higher potential for commercial use and consumption due to their nutraceutical quality. Most of the fruits of the 20 samples of hawthorn presented a content of phenolic compounds higher than that described for other fruits, these nutraceutical characteristics provide an added value to the product.